Biomarkers in nereis diversicolor (Polychaeta: Nereididae) as management tools for environmental assessment on the southwest Iberian coast - Gomes, Tânia (2013)
The environmental quality of the southwest Iberian coast was assessed in different areas (Ria Formosa Lagoon, Guadiana Estuary and Cadiz Bay) focusing on metal contamination (Cd, Cu, Ni, Pb and Zn) in Nereis diversicolor whole tissues. In addition, associated toxicological effects were assessed using a multibiomarker approach combining several conventional biomarkers. The set of biomarkers selected included antioxidant enzymes (catalase, superoxide dismutase and glutathione peroxidase), metallothionein and lipid peroxidation. N. diversicolor from the Ria Formosa Lagoon, Guadiana River and Cadiz Bay responded differently to metal contamination with different biomarker responses showing a clear site trend, suggesting different sources and/or magnitudes of contamination. Cadmium was a source of oxidative stress in polychaetes, mainly in Cadiz Bay, with a significant influence on antioxidant enzymes and enhancement of lipid peroxidation. The highest MT concentrations were in the Ria Formosa Lagoon and in the Guadiana River, where there was a direct relationship with high nickel concentrations. Biomarker responses of N. diversicolor are useful tools for environmental quality assessment on the southwest Iberian coast, and more specific metal biomarkers should be included in future assessments.